ETIKA PROFESI AUDITOR DALAM MEMODERASI PENGARUH INDEPENDENSI DAN KOMPETENSI AUDITOR ATAS KUALITAS AUDIT - Farah Latifah Nurfauziah; Fitria Ningrum Sayekti; Citra Kharisma Utami (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2021)
The purpose of this study is to identify: (1) the effect of competence and independence of auditors on audit quality, (2) how auditor ethics moderates the effect of auditor competence and independence on audit quality. The sample of this study was 50 representatives of public accounting firm auditors in the city of Bandung. The validity and reliability of the questionnaire were tested before the study. The prerequisite tests for the analysis carried out were the normality test, the multicollinearity test, and the heteroscedasticity test. The data analysis method used is simple regression analysis and multiple regression analysis. The results show that H1 is rejected where there is no effect of Auditor competence on Audit Quality because the regression coefficient is 0.05 and the tcount is 0.365 ttable 2.0452. The results of the H2 test also show that there is no effect of auditor independence on audit quality because the regression coefficient is 0.222 and the tcount is 1.407 ttable 2.0452. While the H1a test shows that Auditor Ethics moderates the effect of Auditor competence on audit quality positively with a significance of 0.034. The H2a test shows that Auditor Ethics does not moderate the effect of Auditor independence on audit quality with a significance value of 0.399.